PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN IPAS MATERI KEKAYAAN BUDAYA INDONESIA WILAYAH SUMATERA UTARA KELAS IV MIS AL WASHLIYAH ARAPAYUNG - Tria Ramadani; Tiflatul Husna; Hidayat; Dalimawaty Kadir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to produce a product in the form of E-LKPD based on Problem Based Learning (PBL) in the learning of Science on the material of Indonesian Cultural Wealth in the North Sumatra Region to measure the learning outcomes of fourth grade students of MIS Al Washliyah Arapayung. This research is a development research (Research and Development). This study uses a 4D development model which is an extension of Define, Design, Development and Dissemination. The instruments used in this study were questionnaires and documentation. The results of the validation/feasibility of E-LKPD from input from material experts, namely lecturers, got a score of 89% from 13 statements and the results of the validation/feasibility of E-LKPD experts, namely lecturers, got a score of 89% from 13 statements. The practicality of E-LKPD based on teacher responses got a score of 92% from 13 statements. The effectiveness of E-LKPD based on student responses got a score of 91% from 6 statements consisting of 16 students. From the validation results data, practicality and effectiveness, the development of E-LKPD based on Problem Based Learning (PBL) in the learning of Science on the material of Indonesian Cultural Wealth in the North Sumatra Region is declared Very Valid or suitable for use as teaching material in the learning process.